Antitrust:: A Necessary Historic Revision - Ramos, André Luiz Santa Cruz (2014)
This article is a brief revisionist study about the history of Antitrust Law, in which we try to demonstrate that, in opposition to what the academic mainstream affirms, the antitrust statutes have not been edited to enforce free competition and/or to maximize the consumer welfare, but to protect inefficient firms who could not survive in a genuine free market, where competition was intense and produced extremely beneficial outcomes for the consumers: constant innovation, increase of production, better products/services and lower prices.